Clientelism: factionalism in the allocation of public resources in Iraq after 2003. Issue 4 (4th July 2018) - Abdullah, Sarwar; Gray, Tim; Clough, Emily
ABSTRACT: This article examines clientelism in Iraq as a case study of one form of corruption. Iraq is an unusual case of corruption, because a key feature of Iraq's corrupt environment is an institutionalised factional political system based on sectarian quotas. The article explores the many links between clientelism and political factionalism, discussing whether clientelism arose because of factionalism, or whether factionalism merely determines the ways that clientelism currently operates in Iraq. Using fieldwork data, the findings show there are two distinct levels of clientelism in Iraq, both of which are linked to political factions: the individual level and the organisational level. First, clientelism at the individual level entails the elites of many political factions regarding 'money politics' as a means of influence in Iraq/Kurdistan by buying people's affiliations and thereby governing people. Second, clientelism at the organisational level entails that the spoils of political office are shared out among the elites of the political factions in a proportionate fashion. The article concludes that clientelism is a form of political rather than economic corruption; and that while there may be some immediate value in clientelism, its long-term harm outweighs its short-term value.